Sarasvatī : riverine goddess of knowledge : from the manuscript-carrying vīṇā-player to the weapon-wielding defender of the Dharma - Ludvik, Catherine (Brill's Indological library, 2007)
Drawing on textual and art historical sources, this book traces the conceptual and iconographic development of the Indian riverine goddess of knowledge Sarasvati from sometime after 1750 BCE to the seventh century CE.